OVERVIEW OF THE LARGEST HEALTH HAZARD: PNEUMONO ULTRAMICROSCOPE –DETECTED SILICOVOLCANOCONIOSIS (Journal of Pharmaceutical Negative Results, 2023)
A lung illness with the longest English word (45 letters) pneumono ultramicroscopic silicovolcanoconiosis Inhaling sand and silica dust can lead to the lung irritation that results in silicosis. The earth's crust has the most silica minerals. Affected individuals are those who breathe in the fine silica dust while working in the mining or construction industries. Silicosis is a degenerative condition that has no known treatment. Infections like mycobacterial infection, fungal infection, and TB are caused by it. This article outlines the several types of silicosis, as well as it historical context, epidemiology, diagnosis and therapy. The progression of silicosis is thought to be intimately related to programmed cell death (PCD), which includes autophagy, apoptosis and pyro ptosis, according to our hypothesis in this review and additionally, proteins plays a significant role in formation and development of silicosis. In conclusion, more in depth study on these mechanism and impact may be anticipated to become interesting candidates for silica therapy or intervention in future[1].